Pengaruh Pembinaan Guru Pendidikan Agama Islam Terhadap Pembentukan Karakter Siswa SMP Negeri 12 Makassar - Angriani Putri, Aisyah; Mustamin, Mustamin; Raehana, Syarifa; Wahab, Abdul (LP2M Universitas Islam Ahmad Dahlan, 2025)
The research findings indicate that Islamic Religious Education teachers have a significant impact on the character development of 9th-grade students at SMP Negeri 12 Makassar. Partially, the three variables-wisdom-based methods, exemplary behavior, and facilitation-showed t-values greater than the t-table values and significance levels below 0.05. Additionally, the overall significance value of 0.0497 is less than 0.05, and the F-value of 0.497 is greater than the F-table value of 0.020, indicating that the alternative hypothesis (Ha) is accepted and the null hypothesis (H0) is rejected. This means that the combination of the three teacher development approaches significantly influences students' character formation. The independent variables contribute 20% to the dependent variable, while the remaining 80% is influenced by other factors not included in this study. These findings highlight the crucial role of PAI teachers in shaping students' character at school